STUDI KOMPARASI GAYA HIDUP MAHASISWA BIDIKMISI DAN NON BIDIKMISI PRODI PENDIDIKAN EKONOMI FKIP UNTAN - Ulfie Dian Mustika; F. Y. Khosmas; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aimed to determine: consumptive lifestyles of bidikmisi students of FKIP UNTAN economic education program, consumptive lifestyles of non-bidikmisi students of FKIP UNTAN economic education program, examine differences in consumptive lifestyles of bidikmisi students and non-bidikmisi study programs FKIP UNTAN economics. This research was comparative study with descriptive quantitative approach. The sample was regular economics study program students a FKIP UNTAN class of 2015-2018 using a random stratified random sampling technique of 136 people. Retrieval of data using questionnaire with a Likert scale and interviews. Data analysis techniques using descriptive analysis and comparative analysis. The results showed that the consumptive lifestyle of bidikmisi students in the low category by 50%, the consumptive lifestyle of non-bidikmisi students in the low category by 52.9%, the probability value (Sig.) was greater than 0,05 (0.524>0.05) so that Ho's decision was accepted and Ha was rejected which reads "There was no difference in consumptive lifestyle between bidikmisi students and non-bidikmisi FKIP UNTAN economic education programs" significantly.Keywords: Lifestyle, Bidikmisi Students, Non Bidikmisi Students